Can trade policies soften the economic impacts of an avian influenza outbreak? simulations from a CGE model on the Philippines - Rodriguez, U-Primo E.; Garcia, Yolanda T.; Garcia, Arnulfo G.; Tan, Reynaldo L. (2007)
The paper examines the possibilities of using trade policy to address the adverse economic effects of an avian influenza outbreak in the Philippines. In particular, it employs a computable general equilibrium (CGE) model for analyzing the likely effects of two options; namely, a) a ban on imported poultry, and b) the removal of tariffs on non-poultry meat products. Using six model scenarios (i.e., production shocks, consumption shocks, ban on poultry imports, removal of tariff on non-poultry imports, and selected combinations of these shocks), the simulation results reveal that (a) the consumption and production shocks are expected to have a contractionary effect on real GDP; (b) the expected fall in the output of poultry products explains most of the decline in real GDP; (c) the production shock appears to have a larger impact since this explains most of the decline in real GDP as well as the increase in the general price level; (d) while the consumption shock tends to have a larger impact on the poultry products, the production shock dominates the aggregate responses because of its effects on other industries, and (e) avian influenza is likely to have far-reaching effects on the economy, way beyond the poultry sector. Based on these results, this paper supports the use of an import ban as a preventive measure against the occurrence of an avian influenza attack. This is based on the finding that the economic costs from such a measure appear to be lower than the costs associated with the disease. In contrast, the study finds that there is a weak case for removing tariffs on non-poultry meat products as a means to soften the harmful impacts of an avian influenza outbreak.
Keywords: Animal industry; International relations; Avian influenza